Efficient Content Based Image Retrieval Using Fuzzy Approach - Dahale Sunil, V; Thorat, SB; Butey, PK; Dhore, MP (International Journal of Computer Sciences and Engineering, 2025)
content based image retrieval (CBIR) has been one of the significant research areas in computer science in the recent time. Various feature like Texture, color & shape are used in CBIR for image retrieval. Basically, color is the most striking feature in the content based image retrieval. Different extraction methods are used in content based image retrieval (CBIR). A retrieval method which is based on color histogram by using fuzzy inference system approach is proposed in this paper. We propose a fuzzy rule based approach with27 rules, for effective image retrieval. The experimental results show the robustness and the efficiency of the proposed system for CBIR.